A Self‐Reconfigured, Dual‐Layered Artificial Interphase Toward High‐Current‐Density Quasi‐Solid‐State Lithium Metal Batteries - Guo, Jun‐Chen; Tan, Shuang‐Jie; Zhang, Chao‐Hui; Wang, Wen‐Peng; Zhao, Yao; Wang, Fuyi; Zhang, Xu‐Sheng; Wen, Rui; Zhang, Ying; Fan, Min; Xin, Sen; Zhang, Juan; et al. (Advanced materials (Weinheim), 2023)
The uncontrollable dendrite growth and unstable solid electrolyte interphase have long plagued the practical application of Li metal batteries. Herein, a dual‐layered artificial interphase LiF/LiBO–Ag is demonstrated that is simultaneously reconfigured via an electrochemical process to stabilize the lithium anode. This dual‐layered interphase consists of a heterogeneous LiF/LiBO glassy top layer with ultrafast Li‐ion conductivity and lithiophilic Li–Ag alloy bottom layer, which synergistically regulates the dendrite‐free Li deposition, even at high current densities. As a result, Li||Li symmetric cells with LiF/LiBO–Ag interphase achieve an ultralong lifespan (4500 h) at an ultrahigh current density and area capacity (20 mA cm−2, 20 mAh cm−2). LiF/LiBO–Ag@Li anodes are successfully applied in quasi‐solid‐state batteries, showing excellent cycling performances in symmetric cells (8 mA cm−2, 8 mAh cm−2, 5000 h) and full cells. Furthermore, a practical quasi‐solid‐state pouch cell coupling with a high‐nickel cathode exhibits stable cycling with a capacity retention of over 91% after 60 cycles at 0.5 C, which is comparable or even better than that in liquid‐state pouch cells. Additionally, a high‐energy‐density quasi‐solid‐state pouch cell (10.75 Ah, 448.7 Wh kg−1) is successfully accomplished. This well‐orchestrated interphase design provides new guidance in engineering highly stable interphase toward practical high‐energy‐density lithium metal batteries. A spontaneously reconfigured, dual‐layered artificial interphase of LiF/LiBO–Ag is proposed to stabilize Li anode at high current densities. The LiF/LiBO top layer guarantees fast Li‐ion transition, and the lithiophilic Li–Ag bottom layer enables uniform Li deposition. Benefiting from the well‐orchestrated interphase design, the quasi‐solid‐state lithium metal batteries demonstrate a high practical specific energy (448.7 Wh kg−1), superior high‐rate performances, and high safety.